Visual and cerebral sequelae of very low birth weight in adolescents. Issue 4 (21st February 2007) - Hellgren, K; Hellström, A; Jacobson, L; Flodmark, O; Wadsby, M; Martin, L
Abstract : Objective: To describe the visual functions and relate them to MRI findings and the intellectual level in adolescents born with very low birth weight (VLBW). Design: Population-based case–control study. Patients: 59 15-year-old VLBW adolescents and 55 sex and age-matched controls with normal birth weight. Main outcome measures: Objective clinical findings (visual acuity, stereo acuity and cycloplegic refraction) were recorded. Structured history taking was used to identify visual difficulties. The intellectual level was assessed with the Wechsler Intelligence Scale for Children (WISC). All VLBW adolescents underwent MRI of the brain. Results: Significant differences were found between the VLBW adolescents and controls regarding visual acuity (median −0.11 and −0.2, respectively; p = 0.004), stereo acuity (median 60″ and 30″, respectively; p<0.001), prevalence of astigmatism (11/58 and 0/55, respectively; p<0.001) and in full-scale IQ (mean IQ 85 and 97, respectively; p<0.001) and performance IQ (mean 87 and 99, respectively; p = 0.002). The structured history also revealed a borderline significant difference between the groups (mean problems 0.46 and 0.15 respectively; p = 0.051). 30% (17/57) of the VLBW adolescents had abnormal MRI findings and performed worse in all tests, compared with both the VLBW adolescents without MRI pathology and the normal controls. Conclusion: This study confirms previous observations that VLBW adolescents are at a disadvantage regarding visual outcome compared with those with normal birth weight. In 47%, visual dysfunction was associated with abnormal MRI findings and in 33% with learning disabilities. The adolescents with abnormal MRI findings had more pronounced visual and cognitive dysfunction. The findings indicate a cerebral causative component for the visual dysfunction seen in the present study.